2022
DOI: 10.1002/joc.7759
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dry and heavy rainfall days and their projected changes over Northeast Brazil in Coupled Model Intercomparison Project Phase 6 models

Abstract: The Northeast Brazil (NEB) is considered a region that is strongly vulnerable to extreme rainfall events due to climate change. In this context, this study evaluates the performance of 12 general circulation models (GCMs) from the Coupled Model Intercomparison Project Phase 6 (CMIP6) in representing the number of dry (DD) and heavy rainfall days (HRD) over NEB in the historical period and their projections for the near (2016-2040) and far future (2076-2100) under three Shared Socioeconomic Pathways (SSP2-4.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 111 publications
3
10
0
Order By: Relevance
“…On the other hand, the models and the observations show high consistency in increasing drought events in the NES region. All of the above align with previous studies (Almeida et al 2017 ; da Silva et al 2019 ; Olmo and Bettolli 2021 ; Solman et al 2021 ; Medeiros and Oliveira 2022 ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…On the other hand, the models and the observations show high consistency in increasing drought events in the NES region. All of the above align with previous studies (Almeida et al 2017 ; da Silva et al 2019 ; Olmo and Bettolli 2021 ; Solman et al 2021 ; Medeiros and Oliveira 2022 ).…”
Section: Resultssupporting
confidence: 91%
“…15 . Studies that have found similar results (Ge et al 2021 ; Medeiros and Oliveira 2022 ; Santos et al 2019 ) conclude that this could imply a potential risk of intensified extreme rainfall, which would accentuate the vulnerability of various socioeconomic sectors, such as agriculture, water management, forests and, disasters preparedness.
Fig.
…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations